ANALISIS KUALITAS PRODUK, KUALITAS PELAYANAN, DAN HARGA TERHADAP KEPUASAN DAN LOYALITAS PELANGGAN (STUDI KASUS PADA SOERABI BANDUNG ENHAII CABANG RAWAMANGUN) - Lilik Trianah; Diah Pranitasari; Tutut Esti Rahmanasari (MEDIA STUDI EKONOMI, 2017)
This research goal is knowing the effect of product quality, service quality, and price toward satisfaction and customers loyalty of Soerabi Bandung Enhaii Rawamangun branch. Sampling technique of this research is purposive sampling with 110 total sample. Data analysis method on this research is path analysis.The result of this research showed that the positive effect of product quality toward customer satisfaction is 0,249. The positive effect of service quality toward customer satisfaction is 0,179. The positive effect of price toward customer satisfaction is 0,192. The positive effect of product quality toward customer loyalty is 0,246. The result of this research showed that service quality has no positive effect toward customer loyalty . The positive effect of price toward customer loyalty is 0,221. The result of research showed that customer satisfaction has no positive effect toward customers loyalty. The effect of product quality, service quality and price toward customer satisfaction together are 0,139. The effect product quality, service quality, price, and customer satisfaction toward customer loyalty together are 0,123.Keyword : Product Quality, Service Quality, Price, Customers Satisfaction and Customers Loyalty